In vivo molecular imaging with cetuximab, an anti-EGFR antibody, for prediction of response in xenograft models of human colorectal cancer - Goetz, M.; Hoetker, M. S.; Diken, M.; Galle, P. R.; Kiesslich, R. (Endoscopy, 2013)
Background and study aims: Molecular imaging has mainly been studied for detection of lesions using diagnostic probes. The aim of the current trial was to evaluate in vivo confocal laser endomicroscopy (CLE) with cetuximab, an antibody targeting the epidermal growth factor receptor (EGFR), for detection and moreover early prediction of response to molecular chemotherapy in models of human colorectal cancer (CRC).Methods: Xenografts with cetuximab-sensitive (HT29) and cetuximab-resistant (SW620) human CRC cell lines were induced in 44 mice. CLE was performed 48 h after injection of a fluorescently labelled cetuximab test dose, and compared with isotype antibody or untreated controls on d0, and d30 (HT29) or d15 (SW620). Initial fluorescence intensity was examined in relation to clinical readouts (tumor growth, thriving, mortality) during cetuximab treatment vs. controls. Results were validated in vivo with wide-field molecular imaging in three HT29 mice and ex vivo using fluorescence-activated cell sorting (FACS) and immunohistochemistry.Results: All HT29 xenografts showed specific fluorescence in vivo after cetuximab injection on d0 and d30. Fluorescence at d0 was significantly stronger in cetuximab-treated HT29 tumors than in HT29 controls (P = 0.0017) or cetuximab-treated SW620 tumors (P = 0.0027), and accorded with significantly slower tumor progression (P = 0.0009), better overall survival (P = 0.02), and better physical condition (P < 0.0001). Cetuximab sensitivity could be predicted from fluorescence intensity at d0 with high positive predictive value.Conclusions: Molecular CLE was for the first time linked to early prediction of response to targeted therapy in models of human CRC. Therapeutic antibodies can be used as molecular beacons in CLE and wide-field techniques. These results may indicate a promising principle for early patient stratification.